Airspace Delegation: Preserving Indonesia Territorial Sovereignty through Flight Information Regions Realignment - Sitamala, Afandi (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
"He who commands the skies commands all." General Giulio Douhet's renowned 1921 quote resonates even a century later. On January 25, 2022, Indonesia and Singapore settled longstanding bilateral issues, including aviation needs and safety. A crucial aspect was the realignment of their flight information regions (FIRs). This paper delves into the FIR concept, emphasizing the delicate balance between air safety and territorial sovereignty. The FIR agreement safeguards Indonesia's sovereignty while fostering collaboration with Singapore in airspace management. However, it has sparked debates on specific aspects, especially the limited delegation of airspace to Singapore. The intricacies of delegating airspace management have fueled discussions. Additionally, concerns have emerged about the FIR's impact on maritime security operations, given that reporting to the Singapore FIR allows monitoring of maritime security vessels.